PENGARUH SEDUHAN BAWANG PUTIH TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI : LITERATUR REVIEW - Sunarno, Rita Dewi; Syarif, Ahmad (NHM PRESS, 2023)
Hypertension is an increase in systolic blood pressure greater than or equal to 140 mmHg, and an increase in diastolic pressure greater than or equal to 90 mmHg. Hypertension is a health problem in all parts of the world and is a major risk factor for cardiovascular disease. One of the non-pharmacological therapies that can be applied to lower blood pressure is using a decoction of garlic which contains allicin which is efficacious as an antihypertensive. This study aims to conduct a literature review related to the effect of steeping garlic on reducing blood pressure in hypertensive patients. This literature study uses the literature review method. Search for articles or journals using keywords (AND, OR NOT) that are used to expand or specify. The keywords used in this study were